RELASI GENDER BATARI TOJA DAÉNG TALAGA DALAM KONTEKS SOSIAL POLITIK BUGIS BERDASARKAN LONTARAQ - Andi Hilda (JURNAL ILMU BUDAYA, 2020)
This study aims to analyze the gender relations contained in the text of Lontaraq Attoriolong Bone, especially the role of Batari Toja Daéng Talaga in the socio-political environment. This research is a qualitative study using descriptive methods using equilibrium theory to analyze the gender relations of Batari Toja Daéng Talaga in carrying out socio-political roles. In this study, researchers used a research method in the form of library research. A literature study is carried out through data collection or scientific writing aimed at the object of study or collection of library data, or analysis carried out to solve a problem which rests on a critical and in-depth study of relevant library materials. The results showed that the BTDT gender elation in socio-political roles in the Lontaraq Attoriolong Bone manuscript found no differences between the roles of men and women.